Quality changes in sugar beet (Beta vulgaris L.) roots during storage period in piles - Al-Jbawi, Entessar; Geddawi, Sameer Al; Alesha, Gaidaa (International Journal of Environment, 2015)
Root transportation or remaining in fields or trucks for many days before manufacturing is considered one of the main problems that leads to the deterioration of root quality, and caused a great loss for the farmer and government. Because of the importance of this issue, a study was conducted during 2007 and 2008 seasons at winter time (15th of Jan) at Al Ghab Agriculture Research Center, General Commission for Scientific Agricultural Research (GCSAR), Syria, to determine the effect of some agricultural treatments (varieties), and environment conditions on the quality traits, water content of sugar beet during 1-10 days after harvest. Also to estimate correlation coefficient between post harvest period and the quality traits and water content. Four recommended sugar beet varieties were used, tow monogerm i.e. Rizor and Sherif, and tow multigerm i.e. Hospoly and Kronos. Randomized Completely Block Design (RCBD) was used with four replicates. The results showed that prolonging storage period of the harvested roots leads to high and gradual increment in the total soluble solids (brix %), from the first day to the last day of the studied storage period. The percent of increment for all varieties in brix% was 42.98%. Also the results clarified low sugar percent, and water content, which were 46 and 21.25 %, respectively. The reduction in juice purity % ranged from 76.08% in the first day to 67.23% in the last day for all varieties. The coefficient of correlation (r) exhibited a positive correlation between brix % and sucrose % , and a negative correlation between brix % and purity %, and also a negative correlation between water content and both brix and sucrose percentages. International Journal of Environment Vol.4(4) 2015: 77-85